2021
DOI: 10.3390/ijerph18147455
|View full text |Cite
|
Sign up to set email alerts
|

Please Like Me: Ingratiation as a Moderator of the Impact of the Perception of Organizational Politics on Job Satisfaction

Abstract: Drawing from the negative impacts of the perception of organizational politics (POP) on the literature on organizational outcomes, the model proposed in this study examines a nonlinear relationship of POP on job satisfaction. In a similar way, ingratiation as a moderator variable is tested. Based on a survey of 240 state-owned enterprise employees in Indonesia, this study finds that POP exhibits an inverted U-shaped relationship with job satisfaction. Low and high levels of POP have a negative impact on job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 86 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…Students utilised ingratiation when communicating privately with staff. Help-seeking research highlights that ingratiation is effective in reaping positive feedback (Metzler and Scheithauer, 2018) especially when associated with being liked (Fitriastuti, et al, 2021). When contacting staff privately, the nature of the communication is more personal and so the desire to be liked may be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Students utilised ingratiation when communicating privately with staff. Help-seeking research highlights that ingratiation is effective in reaping positive feedback (Metzler and Scheithauer, 2018) especially when associated with being liked (Fitriastuti, et al, 2021). When contacting staff privately, the nature of the communication is more personal and so the desire to be liked may be elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when controlling for ingratiation that is performed within the organisation, they found that ingratiation performed externally was positively related to the manager's decisions about bonus allocations and promotions. In another study, Fitriastuti, Larasatie, and Vanderstraeten (2021) found that using ingratiation as an impression management tactic strengthens the effects of perception of organisational politics on job satisfaction.…”
Section: Theoretical Framework On Impression Managementmentioning
confidence: 95%
“…This act is motivated by supervisors' status and control over important work resources [36]. Ingratiation is also employed as a coping mechanism and adaptive strategy when workers perceive high degrees of organizational politics [37].…”
Section: Impression Management and Workplace Exclusionmentioning
confidence: 99%